Optimization of electric power wireless communication technology - Xunwei ZHAO; Jie BAI; Gaoquan DING; Liyu XIANG (Dianxin kexue)
An optimized design for improving spectral efficiency was given for the case where the power wireless private network in the 230 MHz band continuously allocates carriers.By canceling the reserved guard band between carriers,continuous subcarrier frequency domain resource mapping,adaptive FFT and filtering processing were used,which reduced the amount of computation and improves the service rate.Aiming at the problem of unification of two technical standards of 230 MHz power wireless private network,the necessity and the preliminary analysis of the mature terminal and system equipment industry chain of public network were given.